Lupus-specific antibodies reveal an altered pattern of somatic mutation. - Manheimer-Lory, A J; Zandman-Goddard, G; Davidson, A; Aranow, C; Diamond, B (The Journal of Clinical Investigation, 1997)
The F4 idiotype is a heavy chain determinant expressed almost exclusively on IgG immunoglobulins and is highly associated with specificity for double-stranded DNA. Since high-titered F4 expression is present predominantly in sera of patients with systemic lupus erythematosus (SLE), we thought F4+ IgG antibodies might constitute a useful subset of immunoglobulins in which to investigate lupus-specific alterations in variable (V) region gene expression or in the process of somatic mutation. This molecular analysis of F4+ B cell lines generated from lupus patients demonstrates that despite the strong association of F4 reactivity with specificity for native DNA, there is no apparent VH gene restriction. Furthermore, VH gene segments encoding these antibodies are also used in protective immune responses. An examination of the process of somatic mutation in F4+ antibodies showed no abnormality in frequency of somatic mutation nor in the distribution of mutations in complementarity-determining regions or framework regions. However, there was a decrease in targeting of mutations to putative mutational hot spots. This subtle difference in mutations present in these antibodies may reflect an intrinsic defect in mutational machinery or, more likely, altered state of B cell activation that affects the mutational process and perhaps also negative selection.